Murder in the Latin Quarter [large type] - Black, Cara, 1951- (Black, Cara, 1951- Aimée Leduc investigation., 2009)
When a Haitian woman arrives at the office of Leduc Detective and announces that she is Aimée's sister, her father's illegitimate daughter, Aimée is thrilled. A virtual orphan since her mother's desertion and her father's death, she has always wanted a sister. Her partner, René, however, is wary. Under French law even an illegitimate child would be entitled to a portion of her father's estate, including the detective agency and Aimée's apartment.